ST37 Steel Carburization with Coconut Charcoal - Sebayang, Melya Dyanasari (Talenta Publisher, 2021)
The carburization process is a surface hardening process where carbon is added to the surface without changing the core properties of the material. This process is carried out at the austenite temperature so that the carbon can diffuse into the phase. This process can only be done on low carbon steels with content below 0.25%. This research was conducted on ST37 steel, which is steel with low carbon content with 0.18% carbon content. This type of steel is surface hardened with a carburizing temperature of 850 C with a long lasting time of 1 hour, then it is carried out under moderate cooling with outside air media. And change its mechanical properties from the comparison of the initial mechanical properties of the specimen. The highest hardness value occurs in the carburizing process of coconut shell charcoal, but this hardness value occurs not because of the carburization process but because of the enlarged grain size caused by heating at temperatures below 723â° C, thus reducing the elongation properties of the material. Carburizing with battery stone media is more efficient than coconut shell charcoal at temperatures below 723 C. Because the temperature is below the austenite temperature, the absorbed carbons cannot diffuse as happened in the carburization process, but the absorbed carbons can bind the grain boundaries and change their hardness by 4%. In the microstructure research that occurs in this process nothing can change its phase because the temperature does not reach the austenite temperature. However, there are differences in the microstructure between the carburization process with coconut shell charcoal media.